The rise of China and India in Africa : challenges, opportunities and critical interventions - Fantu Cheru, 1949-; Obi, Cyril (Africa now (Zed Books), 2010)
This book examines in detail the opportunities and challenges posed by the increasing presence of China and India in Africa, and proposes critical interventions that African governments must undertake in order to negotiate with China and India from a stronger and more informed platform.